Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1016/j.dadm.2014.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral testing affects the phenotypic expression of APOE ε3 and APOE ε4 in targeted replacement mice and reduces the differences between them

Abstract: Apolipoprotein E4 ( APOE ε4) is the most prevalent genetic risk factor for Alzheimer's disease (AD). Targeted replacement mice that express either APOE ε4 or its AD benign isoform, APOE ε3, are used extensively in behavioral, biochemical, and physiological studies directed at assessing the phenotypic effects of APOE ε4 and at unraveling the mechanisms underlying them. Such experiments often involve pursuing biochemical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 47 publications
1
4
0
Order By: Relevance
“…Together, these previous findings may help to explain the cognitive impairments exhibited by mice lacking ApoE or expressing ApoE4 particularly in spatial learning/memory and in olfactory memory, two neurogenic-dependent behaviors [63][64][65][66][67][68][69][70][71]. Although it remains unclear whether recovery from injuries such as TBI is dependent on neurogenesis in general and ApoE state in particular, the present study adds needed insight into a potential mechanism linking the two.…”
Section: Plos Onesupporting
confidence: 54%
“…Together, these previous findings may help to explain the cognitive impairments exhibited by mice lacking ApoE or expressing ApoE4 particularly in spatial learning/memory and in olfactory memory, two neurogenic-dependent behaviors [63][64][65][66][67][68][69][70][71]. Although it remains unclear whether recovery from injuries such as TBI is dependent on neurogenesis in general and ApoE state in particular, the present study adds needed insight into a potential mechanism linking the two.…”
Section: Plos Onesupporting
confidence: 54%
“…Hence, it is not surprising that impairments in performance in hippocampus-dependent behavioral tasks in mice deficient in ApoE or ones carrying the human ApoE4 are observed. Several studies have demonstrated that the presence of human ApoE4 or the absence of rodent ApoE impaired odor memory, Morris water maze task, and contextual fear-conditioning tasks ( Masliah et al, 1997 ; Grootendorst et al, 2001 ; Peister et al, 2006 ; Rodriguez et al, 2013 ; Salomon-Zimri et al, 2015 ; Peng et al, 2017 ; East et al, 2018 ). Further studies are required to determine the electrophysiology of newborn neurons under such genetic backgrounds to see whether they mimic the deficits in behavioral performance.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, genetic inhibition of the CypA–MMP-9 pathway at the BBB reversed neurodegenerative changes in Apoe −/− mice ( Bell et al, 2012 ). Because Apoe −/− ( Raber et al, 1998 ; Bell et al, 2012 ; Lane-Donovan et al, 2016 ) and APOE4 transgenic mice ( Bell et al, 2012 ; Salomon-Zimri et al, 2014 , 2015 ; Liu et al, 2015 ) develop behavioral deficits at 4–6 mo of age after BBB breakdown, collectively, these findings suggest that BBB breakdown ( Table 2 ) not only contributes to neuronal changes in these models but also is an important therapeutic target.…”
Section: Bbb Breakdown In Apoe Transgenic Modelsmentioning
confidence: 99%